1994
DOI: 10.1212/wnl.44.4.652
|View full text |Cite
|
Sign up to set email alerts
|

Interrater agreement for diagnosis of Alzheimer's disease

Abstract: There are standardized criteria to assist in the diagnosis of Alzheimer's disease (AD), a disorder that lacks unique clinical, morphologic, or biochemical features. Diagnostic reliability of single groups of investigators using these criteria is moderate to substantial. In this study, seven clinicians at separate sites established a criteria-based diagnosis in 42 consecutive memory disorder patients participating in a national genetic epidemiologic study using a quantitative multiaxis AD rating scale (ADRS) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…4,6,[13][14][15] Specifically, we used two sources of information to develop these risk curves: (1) gender-and age-specific incidence curves for first-degree relatives of persons with AD (comparable to those previously published in Green et al, 4 Cupples et al, 14 and Lautenschlager et al 15 ). and (2) APOE genotype-specific odds ratio estimates for each gender and age reported in a meta analysis of data from over 50 studies worldwide.…”
Section: Methodsmentioning
confidence: 99%
“…4,6,[13][14][15] Specifically, we used two sources of information to develop these risk curves: (1) gender-and age-specific incidence curves for first-degree relatives of persons with AD (comparable to those previously published in Green et al, 4 Cupples et al, 14 and Lautenschlager et al 15 ). and (2) APOE genotype-specific odds ratio estimates for each gender and age reported in a meta analysis of data from over 50 studies worldwide.…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of the diagnosis of AD is moderate (generalized kappa's in the 0.51 to 0.73 range) in Class II studies. [8][9][10] When standardized clinical diagnostic criteria are used, interrater reliability 6 and consistency of diagnosis between the initial visit and 1-year follow-up is high (95% in Forette 11 ). There are 13 studies, 3 Class I 12-14 and 10 Class II, 9,[15][16][17][18][19][20][21][22] that have addressed the diagnostic accuracy of the clinical diagnosis of AD using neuropathologic confirmation as the "gold standard."…”
Section: Are Current Diagnostic Criteria Able To Establish a Diagnosimentioning
confidence: 99%
“…The MIRAGE study is the largest genetic epidemiological study of its kind to date, focusing on both African American and white families. 13,14,65 As a result, it provided a potential basis for clarifying risk profiles for African Americans and risk estimates to FDRs of persons with AD. The study found significantly higher risk for dementia among FDRs of African Americans compared with whites (RR 1.6; 95% CI 1.4 -1.9).…”
Section: The Mirage Studymentioning
confidence: 99%
“…The MIRAGE study recruited patients with AD from 17 specialty clinics between May 1991 and March 2001, using methods published elsewhere. 14,65,79 The dementia risk models stratified by ethnicity as presented by Green et al 13 provided a basis for creating AD models for the REVEAL study.…”
Section: Feasibility and Creation Of Customized Risk Curvesmentioning
confidence: 99%